The Influence of Customer Experience, Service Quality, and Perceived Value on Customer Satisfaction: A Systematic Literature Review - Jati Susatya Wijanegara; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of customer experience, service quality, and perceived value on customer satisfaction through a Systematic Literature Review (SLR) approach. The research method used is a literature review (library research) with a descriptive qualitative approach. Data were obtained from various scientific articles sourced from Google Scholar, Mendeley, and other academic databases, using criteria for relevant and credible publications. The results indicate that customer experience plays a role in shaping emotional and cognitive perceptions that influence customer satisfaction. Service quality was found to be a key factor determining satisfaction through the alignment between customer expectations and service performance. Additionally, perceived value also has a significant influence on satisfaction levels based on customers’ evaluation of the benefits received relative to the costs incurred. In conclusion, these three variables consistently have a positive influence on customer satisfaction, although other factors such as brand image, trust, and customer loyalty may also play a role